Fragile Übergänge Junge Männer, Gewalt und HIV/AIDS - Zur Bewältigung chronischer Arbeitslosigkeit in einem südafrikanischen Township - Forcher-Mayr, Matthias (Thesis series, 2014)
HIV/AIDS and violence form a twofold epidemic in South Africa. The experience of chronic unemployment and the subsequent inability to live up to a normative concept of male adulthood, to which respectable work is central, supports self-performances which prominently feature the properties of sexual risk behaviour and sexualised violence. In this book the author focuses on the urban space of the township and employs a perspective which combines the subjective experience of male youth transitions with a structural perspective. This approach a follows gendered youth perspective and sheds new light on the social and economic dimensions of the South African HIV/AIDS epidemic and beyond. - HIV/AIDS und Gewalt bilden eine zweifache Epidemie in Südafrika. Die Erfahrungen chronischer Arbeitslosigkeit und des Nicht-Erreichens normativer Vorstellungen männlichen Erwachsenseins zeitigen Selbstinszenierungen, die zentral durch sexuelles Risikohandeln und geschlechtsbezogenes Gewalthandeln realisiert werden. Der Autor nimmt erstmals die subjektive Seite männlicher Übergänge und deren strukturelle Rahmenbedingungen gemeinsam in den Blick - die Grundlage der Betrachtung bietet dabei der soziale Raum des Townships. Die Relevanz der so gewonnenen Perspektiven auf die sozialen Hintergründe der HIV/AIDS-Epidemie reicht weit über Südafrika hinaus.